Optical Coherence Tomography Angiography in Pediatric Myopia and Amblyopia: A Review of Clinical Applications, Microvascular Biomarkers, and Treatment Monitoring - Jiajun Wang; Daohuan Kang; Huixia Hua; Caiping Shi; Yiguo Pan; Yongwei Guo; Wen Sun (Current Medical Imaging Formerly Current Medical Imaging Reviews, 2026)
Abstract: Optical Coherence Tomography Angiography (OCTA) provides depth-resolved imaging of the retinal vascular system without invasion. Its rapid and non-invasive characteristics make it a promising tool for pediatric retinal imaging. Pediatric myopia and amblyopia can affect visual development and long-term visual prognosis. Early identification and dynamic monitoring are of great clinical significance. This paper retrieved English literature published from January 2006 to May 2026 in PubMed and Web of Science, and reviewed the application of OCTA in pediatric myopia and amblyopia. Existing studies show that pediatric myopia is characterized by decreased retinal vascular density (VD), thinner choroidal thickness (CT), and changes in choroidal perfusion parameters; amblyopia is mainly manifested as decreased retinal VD, but results for the foveal avascular zone (FAZ) and choroidal-related indicators are inconsistent. At present, there are still some deficiencies in the research, such as limited sample size, non-uniform equipment and scanning protocols, and lack of long-term follow-up. OCTA is expected to become an important auxiliary tool for the diagnosis, evaluation, and monitoring of treatment for childhood myopia and amblyopia.